Approach in strengthening patriotism among students through patriotism-based courses - Ku Samsu, Ku Hasnita; Adnan, Zatul Himmah; Ismail, Mohd. Mahadee; Lee, Yok Fee; Ab Majid, Arfah; Ab Razak, Ratna Roshida (Human Resource Management Academic Research Society, 2021)
Patriotism-based courses have been thought to Malaysian students since they were in primary school until they reach tertiary education. Certainly, the general objective of those courses is to inculcate as well as to strengthen patriotism in students. Unfortunately, these courses are always seen as subjects that are boring and dull by the students due to the need to memorise facts and historical events. The combination of quantitative and qualitative nature of this study is therefore aimed to identify the teaching and learning approaches that can attract the students’ interest for this kind of nation building courses, thereby making the learning process fun yet effective. Accordingly, the sample has consisted of 800 respondents from public universities who have taken a Malaysian Nationhood course, as their experiences are important to achieve the objective of this study. The findings were analyzed based on the respondents' feedback on the teaching and learning methods to attract students to patriotism-based courses that were categorized into six approaches, namely, teacher centered, student-centered, interactive, constructivist, collaborative and indirect. This classification is important to assist the educators in choosing the appropriate approach to attract students to patriotism-based courses. So far, there are no studies that have categorized teaching and learning approaches based on the respondents' feedback.